The garden of small beginnings - Waxman, Abbi (New York : Berkley, 2017)
"Not since Good Grief has a book about a young widow been so poignant, funny, original, and utterly believable. A compelling debut novel about loss. Give grief a chance. Lilian Girvan has been a single mother for three years--ever since her husband died in a car accident. One mental breakdown and some random suicidal thoughts later, she's just starting to get the hang of this widow thing. She can now get her two girls to school, show up to work, and watch TV like a pro. The only problem is she's becoming overwhelmed with being underwhelmed. At least her textbook illustrating job has some perks--like actually being called upon to draw whale genitalia. Oh, and there's that vegetable-gardening class her boss signed her up for. Apparently being the chosen illustrator for a series of boutique vegetable guides means getting your hands dirty, literally. Wallowing around in compost on a Saturday morning can't be much worse than wallowing around in pajamas and self-pity. After recruiting her kids and insanely supportive sister to join her, Lilian shows up at the Los Angeles Botanical Garden feeling out of her element. But what she'll soon discover--with the help of a patient instructor and a quirky group of gardeners--is that into every life a little sun must shine, whether you want it to or not
"Young widow Lilian Girvan can't see the garden for the weeds... It's been three years since her husband was killed in a car accident and Lilian is still getting used to being sane--after that one early breakdown. She's happy just being able to get her two girls to school every morning, keep her illustrating job, and catch up on her favorite TV shows with her sister. She's not exactly in a rut; she's just letting the grass grow under her feet. But then Lilian's boss asks her to illustrate a vegetable encyclopedia and signs her up for a vegetable-gardening class. Lilian reluctantly agrees and recruits her kids and sister to join her for some drama-free Saturday mornings, because what could be more relaxing than gardening? Nothing...except that this class is filled with people who like to dig a little deeper than the surface, and an instructor who makes Lillian want to bloom for the first time in years. With her fellow newbie gardeners, Lilian learns what it takes to nurture plants--and friendships. Digging in the dirt, with worms and all, teaches Lilian that sometimes you have to let nature take its course, be it in gardening, in life, or in love.."--
Keywords: Widows -- Fiction; Women illustrators -- Fiction; Single mothers -- Fiction; Gardeners -- Fiction; FICTION / Contemporary Women; FICTION / Family Life; FICTION / Romance / Contemporary; Los Angeles (Calif.) -- Fiction; Domestic fiction; Romance fiction